Ichthyological Research - Kai, Yoshiaki; Yagishita, Naoki; Kume, Gen.; Kokita, Tomoyuki; Matsunuma, Mizuki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Ichthyological Research is an official journal of the Ichthyological Society of Japan and is published quarterly in January, April, July, and November. Ichthyological Research primarily publishes research papers on original work, either descriptive or experimental, that advances the understanding of the diversity of fishes. Ichthyological Research strives to cover all aspects of fish biology, including taxonomy, systematics, evolution, biogeography, ecology, ethology, genetics, morphology, and physiology. Ichthyological Research also publishes timely reviews and commentary on recent progress in active areas of research on fish biology.
Keywords: Ecology; Aquatic ecology; Zoology; Animal systematics; Animal taxonomy; Zoology; Ecology; Animal Systematics/Taxonomy/Biogeography.; Freshwater & Marine Ecology